Reviving the lecture: using visually dynamic approaches to teach physiological concepts - Simon C. Cork; Emma Yhnell (Springer, 2024)
Abstract The educational benefit of the traditional didactic lecture to learners in Higher Education is hotly debated. Given increasing student numbers, existing technical set ups and many logistical concerns, lectures remain the norm in many Higher Education Institutions (HEIs). In this personal view piece, we discuss the benefits, opportunities, and challenges of incorporating dynamic teaching approaches, including "draw-alongs" and animations into undergraduate lectures, typically with large class sizes, to create more engaging and interactive lectures for learners.